The impact of taxes measured by GINI index in Macedonia - Sasho Kozuharov; Vladimir Petkovski; Natasha Ristovska (UTMS Journal of Economics, 2015)
The past decades the problem of income inequality and welfare segregation has presented itself as one of the biggest faults for modern economic systems. Republic of Macedonia as a country in development is presented with a serious challenge into decreasing the income inequality witch has risen for average 4% annually over the past 15 years, according to the GINI index. The problem of income inequality for Republic of Macedonia starches further as the country presents itself as one the highest ranking of income inequality in comparison the South-East European countries. The impact of different types of taxes on the income inequality in Republic of Macedonia measured through the GINI index, the econometric model of regression and correlation was conducted towards determination the type of tax that has the most impact on the income inequality in Republic of Macedonia for the observational period, the Personal income tax have the utmost impact on the income inequality measured through the GINI index.
Keywords: O15; 330; inequality; GINI index; personal income tax; income distribution